2001
DOI: 10.1074/jbc.m010688200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Active Oligomeric State of an Essential Adenine DNA Methyltransferase from Caulobacter crescentus

Abstract: Caulobacter crescentus contains one of the two known prokaryotic DNA methyltransferases that lacks a cognate endonuclease. This endogenous cell cycle regulated adenine DNA methyltransferase (CcrM) is essential for C. crescentus cellular viability. DNA methylation catalyzed by CcrM provides an obligatory signal for the proper progression through the cell cycle. To further our understanding of the regulatory role played by CcrM, we sought to investigate its biophysical properties. In this paper we employed equil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…In experiments involving crosslinking of the BamHI MTase subunits, it was shown that the enzyme in a free state exists as a dimer (Malygin et al, 2001). A similar behavior was observed for adenine M.CcrM from C. crescentus dimerized at physiological concentrations, and the dimerization does not affect DNA methylation (Shier et al, 2001).…”
Section: Introductionsupporting
confidence: 51%
“…In experiments involving crosslinking of the BamHI MTase subunits, it was shown that the enzyme in a free state exists as a dimer (Malygin et al, 2001). A similar behavior was observed for adenine M.CcrM from C. crescentus dimerized at physiological concentrations, and the dimerization does not affect DNA methylation (Shier et al, 2001).…”
Section: Introductionsupporting
confidence: 51%
“…The product was digested with BfaI and SapI and ligated into a custom IMPACT (New England Biolabs) vector placed under the control of a T7 promoter (14) digested with NdeI and SapI. This vector places a self-cleaving intein and chitin binding domain at the C terminus of gp59 and allows affinity purification on a chitin column followed by cleavage of the intein with dithiothreitol (DTT) to yield the wild-type gp59.…”
Section: Methodsmentioning
confidence: 99%
“…CcrM binds to and methylates adenosine in the sequence 5Ј-GANTC-3Ј, where "N" is any nucleotide (167,300). Like EcoDam, CcrM is a functional monomer and acts processively (20), although evidence suggests that it is a dimer at physiologic concentration (234). However, unlike EcoDam, CcrM has a distinct preference for hemimethylated DNA as a substrate, based on the observation that the turnover rate for hemimethylated DNA containing a GANTC target site(s) was significantly higher than that for DNA containing nonmethylated sites (20).…”
Section: Orphan Dna Mtasesmentioning
confidence: 99%